Malaysia network transit route adviser: hybrid didistra's algorithm - Mohd Syafiq, Bachok (2014)
Time past by time, Malaysia has been developed from one stage to another stage. Looking for the transportation in Malaysia, There about too many types of transport that are commonly used either private or public such as car and bus. Most people like to use this kind of transport is because to run away from get stuck on the road or to choose the easiest method to move from one destination to another destination. Nevertheless, train also facing with much of problems right now. The problems are difficulty to find the simplest route, the cost will be increased according to the route chosen and the time is not accurate. This is because there to many option of route to go to each destination. According to this problem MANTRA provide the solution to resolve the problem and help the tourist to plan their journey using Hybrid Dijkstra algorithm in the Mantra System.